John Wilkes : the scandalous father of civil liberty - Cash, Arthur H. (Arthur Hill), 1922-2016 (Yale University Press, 2006)
One of the most colourful figures in English political history, John Wilkes (1726 - 97) is remembered as the father of the British free press, defender of civil and political liberties and hero to American colonists, who attended closely to his outspoken endorsements of liberty. Wilkes's political career was rancorous, involving duels, imprisonments in the Tower of London and the Massacre of St. George's Fields, in which seven of his supporters were shot dead by government troops. And he was equally famous for his 'private' life - a confessed libertine, a member of the notorious Hellfire Club and the author of what has been called the dirtiest poem in the English language. This lively biography draws a full portrait of John Wilkes from his childhood days through his heyday as a journalist and agitator, his defiance of government prosecutions for libel and obscenity, his fight against exclusion from Parliament and his service as lord mayor of London on the eve of the American Revolution. Told here with the force and immediacy of a firsthand newspaper account, Wilkes's own remarkable story is inseparable from the larger story of modern liberties and how they came to fruition.